2021
DOI: 10.1590/1983-21252021v34n202rc
|View full text |Cite
|
Sign up to set email alerts
|

Agro-Economic Indicators for Carrot Under Green Manure in a Semi-Arid Environment

Abstract: Green manuring is an important management strategy in tuberous vegetable production systems, since it improves the physical, chemical and biological properties of the soil and, consequently, increases in crop productivity and ecosystem balance. The objective of this work was to evaluate the agro-economic efficiency of carrot cultivation as a function of Calotropis procera biomass amounts incorporated into the soil during two growing seasons in a semiarid environment. The experiments were conducted in an experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
(17 reference statements)
2
7
0
1
Order By: Relevance
“…Silva et al (2018), when studying the performance of lettuce fertilized with different amounts of roostertree, observed maximum lettuce productivity of 18.16 t ha -1 , when 40.29 t ha -1 of dry biomass of this green manure was added to the soil. Silva et al (2021), when evaluating carrot performance in amounts of roostertree in the same region of this research, observed better agroeconomic efficiency of carrot when 42.81 t ha -1 of roostertree dry biomass was incorporated into the soil.…”
Section: Introductionsupporting
confidence: 50%
“…Silva et al (2018), when studying the performance of lettuce fertilized with different amounts of roostertree, observed maximum lettuce productivity of 18.16 t ha -1 , when 40.29 t ha -1 of dry biomass of this green manure was added to the soil. Silva et al (2021), when evaluating carrot performance in amounts of roostertree in the same region of this research, observed better agroeconomic efficiency of carrot when 42.81 t ha -1 of roostertree dry biomass was incorporated into the soil.…”
Section: Introductionsupporting
confidence: 50%
“…e) The intercropping efficiency was also assessed by the score of the canonical variable Z (Silva et al, 2021), obtained through the bivariate analysis of the variance of the beet commercial productivity and rocket green mass yield. The definitions of the terms of the expressions are presented above.…”
Section: Evaluated Variablesmentioning
confidence: 99%
“…Investigation performed in the attempt to recommend intercropping systems with companion cultures suggest that these systems should be evaluated through bio-economic indices in function of production factors tested in the study to indicate or not their bio-economic feasibility. Among these used indices are: land equivalent ratio (Silva et al, 2018a), actual yield loss (Cecilio Filho et al, 2015), intercropping advantage (Gebru, 2015), productive efficiency index (Bezerra Neto et al, 2010), canonical variable score (Silva et al, 2021), crops aggressivity (Cecílio Filho et al, 2015), competitive ratio (Pinto et al, 2011), gross and net returns (GI and NI), rate of return, and profit margin (Silva et al, 2017). Investigation with rocket, carrot and lettuce polyculture associated in strips under different hairy woodrose quantities in diverse plant populations of the crops showed greater viability and bio-economic return of the polyculture when 25 t ha -1 of the green fertilizer was added to the soil in the population of rocket (R), carrot (C) and lettuce (L) of 50R-50C-50L% of the recommended population in monocropping (Oliveira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of these characteristics of cowpea green grain was in the form of a polynomial model due to the greater availability of nutrients released by increasing the equitable amounts of M. aegyptia and C. procera added to the soil, thus increasing the weight and number of green grains per pod, its productivity and dry mass per area. In addition, this behavior also depends on the synchrony between the release and absorption of nutrients by cowpea plants (SILVA et al, 2021b).…”
Section: Characteristics Of Cowpea Green Grainsmentioning
confidence: 99%